Plant extracellular vesicles: A novel bioactive nanoparticle for tumor therapy - Tan, Zhao-Lin; Li, Jing-Fei; Luo, Hao-Ming; Liu, Yang-Yang; Jin, Ye (Frontiers in Pharmacology, 2022)
Extracellular vesicles are tiny lipid bilayer-enclosed membrane particles, including apoptotic bodies, micro vesicles, and exosomes. Organisms of all life forms can secrete extracellular vesicles into their surrounding environment, which serve as important communication tools between cells and between cells and the environment, and participate in a variety of physiological processes. According to new evidence, plant extracellular vesicles play an important role in the regulation of transboundary molecules with interacting organisms. In addition to carrying signaling molecules (nucleic acids, proteins, metabolic wastes, etc.) to mediate cellular communication, plant cells External vesicles themselves can also function as functional molecules in the cellular microenvironment across cell boundaries. This review introduces the source and extraction of plant extracellular vesicles, and attempts to clarify its anti-tumor mechanism by summarizing the current research on plant extracellular vesicles for disease treatment. We speculate that the continued development of plant extracellular vesicle-based therapeutic and drug delivery platforms will benefit their clinical applications.